PENGARUH PELATIHAN, KOMPENSASI, DISIPLIN KERJA DAN BUDAYA KERJA TERHADAP PRESTASI KERJA KARYAWAN PT. BANK SULTRA CABANG UNAAHA - Yu nila; Irda wati (Yayasan Akrab Pekanbaru, 2019)
This study aims to determine the magnitude of the Effect of Training, Compensation, Work Discipline and Work Culture on Employee Performance at PT. Bank of Southeast Sulawesi Unaaha Branch. The population in this study were all employees of PT. The Unaaha Branch of the Southeast Sulawesi Bank totaling 31 people. The sampling technique uses saturated samples so that the number of respondents is 31 people. The analytical method used in this study is multiple linear regression analysis. The results of this study indicate that partially the variables of training, compensation, and work discipline have a positive and significant effect on work performance, while the work culture variable has a negative and not significant effect on work performance.